(The Effect of Plant-Age on the Oil Composition of Curcuma mangga Val.) - Sait, Salya; Lubis, Enny Hawani (Balai Besar Industri Agro, 1989)
The essential oil obtained from Curcuma mangga rhyzomes, which were collected throughout the harvesting season, in the plant age of 9,10 and 11 months, were studied using gas chromatography and chemical as well as physico-chemical methods. During the period of the highest essential oil yield (the age of 11), the higher the percentages of ocimine the lower the percentages of myrcene and lower ester number, meanwhile the lowest essential oil yield (the age of 10), the higher ester number were found.